Expanding Teacher Comfort Zones: Developing Professionalism - Benzehaf, Bouchaib (Yayasan Visi Intan Permata, 2016)
The age we live in is characterized by a constant flow of information and an ever changing set of skills. Such change produces new challenges for teachers and places new obligations on them. Research also shows that teaching quality is paramount for student success. Teachers are thus required to update their knowledge and refine their teaching skills. The present paper argues for the relevance of Vygotsky’s zone of proximal development (ZPD) to teacher education. More specifically, it makes the point that teachers in the new millennium are called upon more than ever before to extend their ZPDs in order to help their students learn effectively in an age pregnant with new challenges. Starting with a brief overview of the concept of ZPD, the paper moves to argue for its application to teacher education. It also unveils the different stages of developing the ZPTD (zone of proximal teacher development), and the characteristics of proximal teacher development that are bound to impact positively on student learning. It ends with practical suggestions that can improve the ZPTD, like participating in conferences, joining teacher associations, and being involved in action research.